Hormones and immunity in cancer: are thyroid hormones endocrine players in the microglia/glioma cross-talk? - Perrotta, Cristiana; De Palma, Clara; Clementi, Emilio; Cervia, Davide (Frontiers in Cellular Neuroscience, 2015)
Accumulating evidence indicates that the endocrine and immune systems engage in complex cross-talks in which a prominent role is played by thyroid hormones (THs). The increase of resident versus monocyte recruited macrophages was shown to be an important effector of the TH 3,3’,5’-Triiodo-L-thyronine (T3)-induced protection against inflammation and a key role of T3 in inhibiting the differentiation of peripheral monocytes into macrophages was observed. Herein, we report on the role of T3 as a modulator of microglia, the specialized macrophages of the central nervous system. Mounting evidence supports a role of microglia and macrophages in the growth and invasion of malignant glioma. In this respect, we unveil the putative involvement of T3 in the microglia/glioma cell communication. Since THs are known to cross the blood-brain barrier, we suggest that T3 not only exerts a direct modulation of brain cancer cell itself but also indirectly promotes glioma growth through a modulation of microglia. Our observations expand available information on the role of TH system in glioma and its microenvironment and highlight the endocrine modulation of microglia as an important target for future therapeutic development of glioma treatments.